From Policy Mandates to Market Signals: Causal and Dynamic Effects of Carbon Information Disclosure on Firm Value - Runyu Liu; Mara Ridhuan Che Abdul Rahman; Ainul Huda Jamil (International Journal of Financial Studies, 2025)
This study examines the causal and dynamic effects of carbon information disclosure on firm value, using a policy-driven setting in China’s carbon-intensive industries. In 2018, the Ministry of Ecology and Environment implemented a regulatory policy requiring internal carbon accounting and third-party verification for carbon-intensive enterprises, without mandating public disclosure. This exogenous policy shock offers a quasi-natural experiment to investigate how firms in carbon-intensive industries respond to environmental mandates through voluntary disclosure and how such disclosure affects their market valuation. Employing a difference-in-differences framework combined with two-stage least squares estimation, we identify a significant increase in carbon information disclosure following the policy intervention. This disclosure leads to a positive and growing effect on firm value, particularly when sustained over multiple years. Moreover, the valuation effect is moderated by regional environmental regulation: firms in areas with lower enforcement intensity benefit more from disclosure, as the signal is perceived to be more voluntary and credible. These findings provide robust causal evidence on the role of carbon information disclosure in shaping market outcomes under regulatory pressure. The study contributes to the literature on environmental regulation and corporate financial behavior in emerging markets.